Os itinerários formativos no ensino médio: um estudo no município de Santa Maria/RS - Silva, Bruna Tafarel (2021)
The reform of the New High School originated amid several changes in the Brazilian political context and was approved without many related to society or education professionals to Law 13.415 / 17. The New High School proposes that school curricula be composed in two parts, the Basic General Formation present in the Common National Curriculum Base (BNCC) and the Formative Itineraries (IF). The Formative Itineraries are called a set of curricular units offered by educational institutions and networks, such as which enable the student to deepen their knowledge and prepare for the continuation of studies or for the world of work. Our main objectives are: to understand the vision of school administrators from the pilot schools in Santa Maria about the Formative Itineraries, and to know as a favorite of Santa Maria students about the formation itineraries. In order to carry out our research, we carried out semi-structured changes with two school administrators from pilot schools of the New High School in Santa Maria / RS, in order to understand their experiences and opinions about the High School Reform. The technique used to analyze the characteristics is content analysis, from the perspective of the theory developed by Bardin (2011). And to find out how students' favorites by the formatives, we used the large scale Barometer Brazil questionnaire and performed mathematical analysis with the students' answers. As a result of the information with the managers, we saw that the initial proposal that the Training Itineraries would be a different form of certain content and built together with education professionals, through a broad dialogue with all the parties involved, was not fulfilled. The main Training Itinerary that students are from Technical and Professional Training, but it is necessary that the State invests resources and structure massively so that this type of training education is offered equal to all students in the municipality, where comprehensive training is citizenship of students is not compromised.